"Back of house" – focused study on food waste in fine dining: the case of Delish restaurants. Issue 3 (3rd August 2015) - Charlebois, Sylvain; Creedy, Amy; von Massow, Mike
Abstract : Purpose: – The purpose of this paper is to identify the key determinants of back-of-house-based food waste in food service outlets. This case study focuses on Delish restaurants, a well-known restaurant chain in Canada, and aims to provide a clear understanding of food service procurement, kitchen practices, cost management, risk mitigation, menu design and technical literacy needs in hospitality. Some recommendations for future studies are also provided. Design/methodology/approach: – The authors chose an exploratory case study design to guide our investigation on restaurants and food waste, based on Yin's (1994) argument that case studies are the preferred strategy when the "why" questions is being posed and when the focus is on a modern occurrence within a real-life context. Such a design is particularly appropriate for understanding the details and complexity of a phenomenon and its design (Stake, 1995). In this study, research data were collected through multiple points. A semi-structured questionnaire was designed and adopted to collect primary data. The objective of the empirical segment is not to test the applicability of the existing approaches, but rather to study conceptual nuances related to the presented model. A survey study was focused on formal interviews onsite, in two different food service facilities (Restaurant A and B). Findings: – When considering food procurement, supplier relationships were found to not be significant for food waste prevention. Company-wide agreements with specific suppliers prevented individual chefs from creating alterations in their ordering to prevent waste. Order shorting was a somewhat common occurrence. However, most employees did not identify portion size as a large driver of waste. This conclusion conflicts somewhat with studies in this area (Kantor et al., 1997). If there was waste on a plate, it is much more likely to be the starches, which are low-cost items as opposed to high-cost proteins. Research limitations/implications: – This research has its limitations, which present opportunities for future research. First, this case study is based on two case studies which have their weaknesses, especially in the reliability of data collection. In future, even though both restaurants had access to an earlier version of this case, a more structured analysis with performance indicators related to food waste would contribute to the internal validity of the study. The external validity of the proposed back-of-house-based determinant framework would benefit from being empirically tested with a larger sample, as the author cannot imply that this study's findings are transferable to other food service operations. Practical implications: – From a managerial perspective, this study has merit. Arguably, the restaurant industry has a cumulative impact on the environment, economy and society as a whole. As more consumers in the Western world eat away from home, proper food management practices are desirable. Currently, few governments regulate or mandate measures to monitor restaurants' sustainability claims and waste management. As consumer expectations change, the onus falls on food operations to validate and inform patrons on practices behind the scenes. Culinary kitchens are often not visible or accessible for some customers, or even obscure for others. Social implications: – Strategies undertaken by management and chefs are reactive as opposed to proactive strategies. The reactive strategies are only able to identify waste a week after it has occurred through inventory checks. From this point, it may be impossible to identify the cause of the waste to prevent it from happening in the future. In addition, attribution to the cause may be laid on the incorrect individual, which will further exacerbate the social learning of the staff as a whole. Proactive strategies undertaken before waste occurs are more effective. Originality/value: – It must be noted that most of the literature on food waste management in casual-dining restaurants does not cover the key challenges found in the food industry. Most noticeable in the review is that there are very few studies in the literature that include food waste management practices linked to distribution management. This area of interest within the hospitality industry has not been well-developed in recent years and requires more attention.